2018
DOI: 10.1177/0957650918781906
|View full text |Cite
|
Sign up to set email alerts
|

Lift and drag force measurements on basic models of low-speed axial fan blade sections

Abstract: This paper presents comparative data on the aerodynamic lift and drag of basic model representations of low-speed axial fan blade sections. Three main types of blades are investigated: flat plate, cambered plate and RAF6-E profiled airfoil. Lift and drag force are measured at three different Reynolds numbers (0.6•10 5 , 10 5 and 1.4•10 5) around the threshold value of 10 5. The measurement data is compared to literature data. The aerodynamic force measurements reveal that, for Reynolds numbers below 10 5 , cam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
2
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 12 publications
1
8
0
Order By: Relevance
“…As already reported in Balla and Vad, 15 the endwall effect may have a significant impact on measurements in closed test section wind tunnels. Mueller 14 also found that the endwall effect may be notable for cambered plates at low Re values.…”
Section: Investigated Casessupporting
confidence: 52%
See 3 more Smart Citations
“…As already reported in Balla and Vad, 15 the endwall effect may have a significant impact on measurements in closed test section wind tunnels. Mueller 14 also found that the endwall effect may be notable for cambered plates at low Re values.…”
Section: Investigated Casessupporting
confidence: 52%
“…Based on this the filtering method established herein focuses on the Re = 60,000 points, which are most likely to be corrupted by the endwall effect. The filtering was applied to those results which were not corrected to infinite span previously, namely the Mueller 14 and own 15 cases (see Table 1). Two types of fit have been made, first the trendlines have been fitted to the data including the Re = 60,000 point.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The extension of existing models is necessary for resolving the trends in measurements on various airfoils and flow conditions. Studies on isolated airfoils are relevant for low solidity fan applications, as discussed in Balla and Vad (2019). In the future, the authors wish to apply the results for the vortex shedding prediction of blade profiles used in the design of low-speed axial fans.…”
Section: Introduction and Objectivesmentioning
confidence: 99%